Cuscuta hyalina Roth (Cuscutaceae) - A new angiospermic record for Bangladesh - Khanam, Mahbuba; Uddin, Mohammad Zashim; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 93, 2003 (December)